Using computers in the law office - Cornick, Matthew S. (Boston, MA Cengage Learning, 2019)
"Equip yourself for career success with this bestselling guide, which explores how computers can make paralegals and legal professionals more productive on the job. USING COMPUTERS IN THE LAW OFFICE, Eighth Edition, provides comprehensive coverage of computer concepts, including the latest versions of common programs like Microsoft Word, Excel, and PowerPoint, and specialized applications such as CaseMap, Clio, HotDocs, TimeMap, and TrialDirector. With a clear and engaging writing style, real-life examples, helpful tutorials, ethical considerations, and detailed hands-on exercises to help you apply what you learn to realistic professional tasks, this proven resource will help you develop the knowledge and skills you need to succeed in today's legal organizations."--
Overview of computers in the law office -- Word processing and document assembly -- Spreadsheet software -- Legal timekeeping and billing software -- Databases, case management, and docket control software -- The cloud and social media -- Electronic discovery -- Litigation support software -- The Internet, computer-assisted legal research, and electronic mail -- The electronic courthouse, automated courtroom, and presentation graphics.
Earlier edition: Roper, Brent D. Using computers in the law office, 5th edition, c2008.
Includes glossary and index (pages 507-523).
Keywords: Law offices -- Automation -- United States; Practice of law -- Automation -- United States; Law offices -- Automation